Acute aortic dissection mimicking a gastric ulcer: Medico‐legal implications - Mesrati, Med Amin (Clin Case Rep, 2019)
The diagnosis of aortic dissection is often difficult because the symptoms are usually non‐specific. AD should be considered in the differential diagnosis of all cases of idiopathic retrosternal pain. Misdiagnosis of AD is a common cause of legal suits in medical practice. Prevention requires a complete and thorough evaluation.